Cultivo e qualidade de sementes de quinoa (Chenopodium quinoa Willd.) em sistema agroecológico e convencional - Belmonte, Cristiani (2017)
The interest for the cultivation of quinoa has been growing worldwide due to the genetic variability of the species, nutritional qualities and adaptation to different climatic conditions. However, the studies with the culture in the country are limited to the cerrado region, being necessary the development of cultivars adapted to edaphoclimatic conditions and to the systems of cultivation of Paraná. Therefore, this study was carried out with the objective of evaluating agronomic characteristics and yield of Chenopodium quinoa Willd genotypes. Of the Quinoa Improvement Program of the State University of Western Paraná. Two experiments were conducted simultaneously in an agroecological production system and a conventional production system in the municipality of Entre Rios do Oeste, in the agricultural harvest of 2015/16. Each experiment was composed of sixteen quinoa genotypes in three replicates, following the randomized block design. The evaluated parameters were number of days for flowering, height of flowering plants, number of plants per linear meter, height of insertion of the first panicle, number of days for maturation and productivity. Afterwards, germination tests were performed at the UNIOESTE Seed Technology Laboratory, in order to evaluate the quality of the agroecological and conventional seeds. The evaluations were at 5 and 8 days after the implantation of the germination test, being quantified the normal and abnormal seedlings, as well as the impurity of the seeds. Genotype Q13-24 was the most suitable for cultivation in the conventional system, and genotype Q13-01 was the most suitable for the agroecological production system. It was observed that there are differences in germination of the genotypes, as well as in the number of abnormal seedlings obtained for each of these. Genotype Q13-21 was among the best seed quality when grown in agroecological and non-conventional systems.